Self-Assessment to Improve the Translation of Biblical Greek - Vera Lecaro, Karen Eunice (2023)
People learn a new language for many different reasons, but most of the time it is learned with the purpose of communication, seeking to integrate conversational and cultural elements to develop linguistic fluency. However, not all languages are meant to be learned for communication. A minority is interested in learning languages that are no longer native to a community, such as Bible translators. They face the difficult task of reproducing not only the grammar and syntax but the meaning of the original text in a way that sounds natural to the reader (Fee & Strauss, 2007). Biblical Greek is one of the languages in which the Bible was originally written. Translating it and interpreting it is fraught with complications; therefore, for the theology student who is new to the matter, learning it becomes very hard. In addition to that, not all have the necessary discipline of perseverance, and give up easily when they do not see progress; making it harder for the teacher to maintain the group's motivation until the end. Furthermore, it is difficult to transfer the relevance of it, and for the professor the easiest route is to tell the student the answers and the meaning of each word, leaving students with the problem of not being able to make sense of it. There is a high need for reinventing the teaching methods of Biblical languages which for very long have been taught through memorization and repetition. Additionally, according to Nikolaeva and Korol (2021), formative assessment should be incorporated to enhance performance and achievement when translating. Through self-assessment students can evaluate the quality of their translation and judge the degree to which their work reflects the criteria needed to build and discuss theology by exegeting the Bible. This paper thus seeks to explore the potential of self-assessment to improve the translation of biblical languages.